Chromatographic and spectral studies of jetsam and archived ambergris. Issue 15 (3rd August 2017) - Rowland, Steven J.; Sutton, Paul A.
Abstract: We describe determination of the dichloromethane-soluble components of 12 samples of the natural product, ambergris, using capillary gas chromatography–mass spectrometry (GC–MS). Ambergris is produced in vivo in about 1% of Sperm whales and is used in perfumery and for odour fixation. Whilst descriptions of ambergris chemistry appeared until about 40 years ago, few accounts of analyses of whole extracts of multiple samples of ambergris by GC–MS have been published before. As expected, our analyses revealed that the major component (up to 97% of the dichloromethane-soluble material) was ambrein, with co-occurring, variable proportions of steroids. Moreover, we report apparently for the first time, mass spectra and retention indices of derivatised ambrein. These data should now allow reliable, rapid confirmation of even small amounts of jetsam, archived museum and customs samples of ambergris and an assessment of ambergris 'quality'. Abstract :